Oxygen Vacancy Injection on (111) CeO2 Nanocrystal Facets for Efficient H2O2 Detection - Tong Li; Qi Wang; Zhou Wang (Biosensors, 2022)
Facet and defect engineering have achieved great success in improving the catalytic performance of CeO2, but the inconsistent reports on the synergistic effect of facet and oxygen vacancy and the lack of investigation on the heavily doped oxygen vacancy keeps it an attractive subject. Inspired by this, CeO2 nanocrystals with selectively exposed crystalline facets (octahedron, cube, sphere, rod) and abundant oxygen vacancies have been synthesized to investigate the synergistic effect of facet and heavily doped oxygen vacancy. The contrasting electrochemical behavior displayed by diverse reduced CeO2 nanocrystals verifies that oxygen vacancy acts distinctly on different facets. The thermodynamically most stable CeO2 octahedron enclosed by heavily doped (111) facets surprisingly exhibited the optimum non-enzymatic H2O2 sensing performance, with a high sensitivity (128.83 µA mM−1 cm−2), a broad linear range (20 µM~13.61 mM), and a low detection limit (1.63 µM). Meanwhile, the sensor presented satisfying selectivity, repeatability, stability, as well as its feasibility in medical disinfectants. Furthermore, the synergistic effect of facet and oxygen vacancy was clarified by the inclined distribution states of oxygen vacancy and the electronic transmission property. This work enlightens prospective research on the synergistic effect of alternative crystal surface engineering strategies.